A control strategy for a grid-connected virtual synchronous generator with virtual impedance - Min’an Tang; Xilin Liu (Energy Reports, 2023)
Virtual synchronous generator (VSG) can simulate synchronous generator turning and damping characteristics, which can further improve the penetration rate of renewable energy in the grid. However, the output impedance of virtual synchronous generator in medium and low voltage microgrids is dominated by resistance, which leads to the coupling of active/reactive power and affects the grid integration control effect, and the phase of VSG and grid voltage will be biased in the absence of a pre-synchronization link. For this purpose, a strategy of grid-connected control of VSG with virtual impedance is proposed. Firstly, the VSG mathematical model is established and virtual impedance is introduced into the VSG electrical portion to improve the grid-connected inverter output characteristics. Secondly, a secondary frequency and voltage regulation strategy to improve VSG control is proposed to restore the frequency and voltage of the VSG, and the SOGI phase-locked loop collects the grid voltage phase to complete the grid-connected pre-synchronization design. Finally, the effectiveness and correctness of the proposed strategy were verified by the simulation results based on MATLAB/ Simulink.